ANALISIS POLA PEMILIHAN JALUR PENDAKIAN PENGUNJUNG DALAM MENDUKUNG BUSINESS INTELLIGENCE PARIWISATA - Mawar Pitri; Harma Oktafia Lingga Wijaya (Jurnal Media Infotama, 2026)
This study aims to analyze visitor behavior patterns in selecting hiking trails at Mount as a basis for decision-making driven by Business Intelligence (BI). The primary issue addressed is the congestion of hikers on specific trails, which risks ecological degradation and diminishes the quality of the tourism experience. This research employs two main methods: Market Basket Analysis (Association Rules) to map hikers' equipment needs based on their chosen trails, and Spatial Zoning Analysis to manage visitor density distribution in real-time.The results indicate a strong association between the "Kawah Hidup" trail selection and the demand for masks, as well as night hiking trails with the rental of flashlights and heavy jackets. Based on these patterns, a service segmentation strategy was developed through four primary packages: "The Adventurer" (Jungle Trail), "The Express Sightseer" (Asphalt Trail), "Summit Explorer" (Gajah Peak & Dead Crater), and "Kawah Hidup Exclusive". Business Intelligence is implemented through digital information boards for zoning management and loyalty programs for local hikers to maintain the sustainability of jungle trails. The conclusion of this research confirms that optimizing logistics stock and digitalizing trail information enhances operational efficiency and supports the ecological sustainability of the Mount forest area.